Transient leukocytosis in Emergency Room: an overlooked issue - Giampiera Bertolino; Federica Quaglia; Luigia Scudeller; Iride Ceresa; Carlo L. Balduini (Italian Journal of Medicine, 2017)
Leukocytosis is regarded as a reliable marker of a serious disorder requiring hospitalization. However, leukocytosis often disappears once the patient is admitted to a medical ward; differential diagnosis of leukocytosis is often overlooked in the busy Emergency Room (ER) routine. We retrospectively evaluated the clinical records of 565 consecutive patients admitted to the Department of Internal Medicine (DIM) after examination in ER. Mean leukocyte count was 11.4×109/L in ER and 10.1×109/L in DIM (P<0.001). Leukocytosis was found in 53.1% of patients in ER, but in 33% of these it was no longer evident on the following day, unrelated to baseline white blood cells (WBC) count, age, sex, diagnosis, C-reactive protein level and early antibiotic treatment. A reduction in WBC count larger than 40% from baseline occurred in 13.6% of all subjects, and in 31.7% of those with transient leukocytosis. Leukocytosis in ER is frequent, but it is often transient and not associated with an infectious cause. Other causes, including psychological stress caused by the ER access itself, should be considered in the differential diagnosis.